(3Mdhd hJbfjGJ (Bphotoshop css - (3YHO GdQMef GdTjH (B.s ((3MdH (B:s (3TYGY ddfTQ h GdYdhe(B,s, 2004)
(3jJfGhd HQfGeL ddJUhjQ GdahJhZQai h GdNOY GdeJbOeI h GdJUejeGJ KdGKjI GdHYO(B.s
(3GdJUejeGJ KdGKjI GdGHYGO(B.s
All age.
Keywords: (3MGSH Bdi (B- (3HQGeL LQGajc(B.s